Active noise control pillow based on the combination of the fixed and adaptive feedback structures. (1st January 2022) - Wu, Lifu; Niu, Feng; Guo, Yecai
Abstract: A portable active noise control pillow based on the combination of the fixed and adaptive feedback structure is built in this paper, where the two structures are decoupled by sharing the same reference signal from the adaptive feedback structure and hence they can be designed independently. Theoretic analysis show that the combination is equivalent to the concatenation of the two structures and thus forms a zero-pole model to approach more complex transfer function. Experimental results confirm that the combined adaptive and fixed feedback structure can achieve better noise reduction performance in comparison with the single fixed or adaptive feedback structure, finally four rules of thumb to use the combined fix and the adaptive feedback structures are provided.